Evaluation of Disc Diffusion Assay for Antifungal Susceptibility of Microsporum canis Strains of Animal Origin from India - Prajapati, Sudhir Kumar; Nair, Sonu Sukumaran; Vijaykumar, Athira; Bablu Kumar; Thomas, Prasad; Premanshu Dandapat; Abhishek (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Dermatophytes are keratinophilic fungi that cause skin infections in both humans and animals. In the current study, 72 Microsporum canis isolates were tested for antifungal susceptibility to seven commercially available antifungal discs (HiMedia), which included clotrimazole (10 μg), amphotericin B (20 μg), nystatin (50 µg), miconazole (30 μg), itaconazole (30 μg), ketoconazole (30 μg), and fluconazole (10 μg). The disc diffusion method was used to assess the antifungal susceptibility of animal dermatophyte isolates. Among all tested isolates fluconazole showed the lowest zone of inhibition, and miconazole as well as clotrimazole were having the highest mean zone of inhibition in M. canis isolates. Although the disc diffusion assays are not frequently used, they will give initial insights into the effective antifungal drugs prior to starting treatment. Antifungal sensitivity testing should be the basis of treatment since dermatophytes are increasingly showing signs of drug resistance to antifungal drugs.